Evaluación del efecto de dos Compost en combinación con un fortificador (wayra) en el cultivo de Maíz Amarillo (zea mays). Yugsiloma, Juan Montalvo, Latacunga, 2017- 2018 - Tucumbi Guashca, María Enriqueta (2018)
At the present researching, the effects of two organic matter in combination with a fortifier (wayra) in the yellow corn crop (Zea mays) under water stress conditions and outside the sowing calendar were evaluated. The research was carried out in the Yugsiloma Sector, Juan Montalvo Parish, Latacunga Canton, Cotopaxi Province, located in the geographic coordinates X = 76879, Y = 9900124 and with an altitude of 2892 meters above sea level. The specific objectives were: Determine the effect of each treatment on the development of the crop (percentage of germination, height, leaf number). Compare the behavior of treatments against the attack of pests and diseases. Determine the phenological behavior of the crop. Within the proposed objectives was carried out in Designing of Random Complete Blocks (DBCA), with four repetitions and four treatments and the test of Tukey significance at 5% and the graph of the phenology of the crop. Through the objectives set for this research it is concluded that the percentage of germination of the four treatments was the T3 that is the fortifier based on wayra silicon with an average of 73.15% of germinated seeds. In the variable height of the plant was the T2 that is the (fortifier based on silicon wayra + cow compost), with an average of 91.45 cm. In the variable number of leaves there was no significance, so an average of 10 to 9 leaves is established. Likewise, the most affected pest was T4, which is the control, with an average of 64.5%. With this research it is concluded that when leaving the sowing calendar there are several difficulties in the development and yield of the crop, because the corn is a seasonal crop and does not support the change of climatic conditions, slowing the life cycle and making it more sensitive to attack by pests and frost.